Brachial plexitis preceding encephalomyelitis in a patient with West Nile virus infection. (5th December 2013) - Scholz, Sonja; Kaas, Bonnie; Simpkins, Alexis; Lyons, Jennifer; Venkatesan, Arun; Probasco, John
Abstract : We describe the case of a 54-year-old woman with West Nile virus infection presenting with painful brachial plexitis and radiculitis that preceded the more typically associated symptoms of meningoencephalitis. Physicians should be aware that West Nile virus infection can present with painful brachial plexitis.